KORELASI ANTARA PRESTASI BELAJAR KEJURUAN DAN ETOS KERJA DENGAN KESIAPAN KERJA DI INDUSTRI OTOMOTIF SISWA KELAS XI TKR SMK MA’ARIF 2 GOMBONG KEBUMEN JAWA TENGAH - Fendi Ariyanto; Suparmin Suparmin (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of the study (1) determine the correlation between the learning achievement of vocational work in the automotive industry readiness class XI student of Mechanical Light Vehicle vocational education Ma'Arif 2 Gombong Kebumen Central Java; (2) determine the correlation between the work ethic to work in the automotive industry readiness class XI student of Mechanical Light Vehicle vocational education Ma'Arif 2 Gombong Kebumen Central Java; (3) determine the correlation between the achievement of vocational learning and work ethic to work in the automotive industry readiness class XI student of Mechanical Light Vehicle vocational education Ma'Arif 2 Gombong Kebumen Central Java.This research was conducted at Vocational High School Maarif 2 Gombong Kebumen Central Java. The population in this study were all students of class XI TKR totaling 123 students and this study using simple random sampling technique with Harry King nomogram calculations to obtain 103 as a sample. This research is correlational and ex post facto categorized. Questionnaire data collection techniques and documentation of learning achievement. The validity of the items were obtained from the product moment correlation. About the reliability of the formula obtained by alpha and declared reliable. Before the data were analyzed first tested the prerequisite analysis is normality test, linearity, and multicollinearity test. Analysis using multiple regression analysis and partial correlation.Based on the analysis of the results obtained the following results: (1) There is a positive and significant correlation between the achievement of vocational learning (X1) to work in the automotive industry readiness class XI student of Light Vehicle Technical Vocational High School Ma'Arif 2 Gombong Kebumen Central Java (Y ); (2) There is a positive and significant correlation between the work ethic (X2) to work in the automotive industry readiness class XI student of Light Vehicle Technical Vocational High School Ma'Arif 2 Gombong Kebumen Central Java (Y); (3) There is a positive and significant correlation between the achievement of vocational learning (X1) and work ethic (X2) to work in the automotive industry readiness class XI student of Light Vehicle Technical Vocational High School Ma'Arif 2 Gombong Kebumen Central Java (Y).